Getting Obligations Right: Autonomy and Shared Decision Making. Issue 1 (24th July 2019) - Lewis, Jonathan
Abstract: Shared Decision Making ('SDM') is one of the most significant developments in Western health care practices in recent years. Whereas traditional models of care operate on the basis of the physician as the primary medical decision maker, SDM requires patients to be supported to consider options in order to achieve informed preferences by mutually sharing the best available evidence. According to its proponents, SDM is the right way to interpret the clinician‐patient relationship because it fulfils the ethical imperative of respecting patient autonomy. However, there is no consensus about how decisions in SDM contexts relate to the principle of respect for autonomy. In response, I demonstrate that in order to make decisions about what treatment they will or will not receive, patients will be required to meet different conditions depending on the approach proponents of SDM take to understanding personal autonomy. Due to the fact that different conceptions of autonomy yield different obligations, I argue that if physicians and patients satisfied all the conditions described in standard accounts of SDM, then SDM would undermine patient autonomy.